THE IMPACT OF LIQUIDITY, LEVERAGE, AND PROFITABILITY ON FIRM VALUE: EVIDENCE FROM POST-PANDEMIC MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2020–2023) - Lu’lu’ul Jannah (CV. Fahr Publishing, 2025)
This study aims to examine the effect of liquidity, leverage, and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research adopts a quantitative method with a causal-comparative approach, using secondary data derived from audited financial statements. A total of 50 companies were selected through purposive sampling. The analytical technique employed is multiple linear regression, supported by classical assumption tests to ensure model reliability. The results indicate that profitability, as measured by Return on Assets (ROA), has a significant and positive effect on firm value, suggesting that companies with stronger earnings are more likely to gain investor trust and achieve higher market valuation. In contrast, liquidity (Current Ratio) and leverage (Debt to Equity Ratio) do not show a statistically significant effect on firm value, highlighting that investors in the manufacturing sector may prioritize profitability over short-term solvency or capital structure. The novelty of this research lies in its integration of recent post-pandemic financial data with a comprehensive model, as well as its focus on the Indonesian manufacturing industry, which is underrepresented in global financial literature. Moreover, the study contributes to validating signaling theory in emerging markets by showing the dominance of profitability as a valuation indicator. In conclusion, managers are encouraged to enhance operational efficiency and profitability to boost firm value, while researchers are urged to explore additional non-financial factors in future studies.